2003
DOI: 10.1016/s0195-668x(02)00823-0
|View full text |Cite
|
Sign up to set email alerts
|

The EuroHeart Failure survey programme—a survey on the quality of care among patients with heart failure in Europe Part 1: patient characteristics and diagnosis

Abstract: Known or suspected heart failure comprises a large proportion of admissions to medical wards and such patients are at high risk of early readmission and death. Many of the basic investigations recommended by the ESC were usually carried out, although it is not clear whether this was by design or part of a general routine for all patients being admitted regardless of diagnosis. The investigation most specific for patients with suspected heart failure (echocardiography) was performed less frequently, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
724
5
80

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,224 publications
(841 citation statements)
references
References 30 publications
32
724
5
80
Order By: Relevance
“…Recent studies, however, have shown that up to 30%-50% of patients admitted with acute HF may have preserved LVEF [14,15,[18][19][20][21]. Patients with preserved LVEF have a high rate of rehospitalisation and a similar, or only slightly lower, mortality, compared to patients with low LVEF [14,15].…”
Section: Systolic Versus Diastolic Left Ventricular Dysfunctionmentioning
confidence: 99%
“…Recent studies, however, have shown that up to 30%-50% of patients admitted with acute HF may have preserved LVEF [14,15,[18][19][20][21]. Patients with preserved LVEF have a high rate of rehospitalisation and a similar, or only slightly lower, mortality, compared to patients with low LVEF [14,15].…”
Section: Systolic Versus Diastolic Left Ventricular Dysfunctionmentioning
confidence: 99%
“…Cerebral symptoms, such as mood changes and intellectual impairment are also common in advanced stages of heart failure (Braunwald et al, 2001;Swedberg et al, 2005). The symptoms may be used to classify the severity of heart failure but often there is a poor relationship between the symptoms and the severity of cardiac dysfunction (Cleland et al, 2003). Resent research shows that left ventricular ejection fraction (LVEF), an important and widely used prognostic variable, is of less importance for predicting outcome in comparison with patients' self-reported symptoms (Ekman et al, 2007).…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…What is more, in Europe, 24% of patients are readmitted within 12 weeks of discharge 2. Some of the most common causes of readmission are deficient treatment adherence, no or too‐late identification of disease destabilization signs, and hospital discharge without complete resolution of congestion 3.…”
Section: Introductionmentioning
confidence: 99%